Causes and characteristics of sudden cardiac death in octogenarians/nonagenarians - Perkiomaki, J; Puolitaival, E; Vahatalo, J; Holmstrom, L; Haukilahti, M A E; Pakanen, L; Ukkola, O H; Junttila, M J; Huikuri, H V (Europace (London, England), 2023)
Abstract Funding Acknowledgements Type of funding sources: Foundation. Main funding source(s): the Finnish Foundation for Cardiovascular Research the Sigrid Jusélius Foundation Introduction The risk for sudden cardiac death (SCD) increases with ageing. Methods We evaluated causes and characteristics of unexpected SCD in SCD victims aged ≥ 80 years in a consecutive series of 5,869 SCD victims who underwent medico-legal autopsy. Results Among SCD victims ≥ 80 years, 91.0% of SCDs were due to ischemic heart disease (IHD) determined in autopsy and 9.0% due to non-ischemic heart disease (NIHD), whereas among those < 80 years, only 72.6% of SCDs were due to IHD and 27.4% due to NIHD (P<.001). Severe fibrosis in myocardium was more common whereas heart weight and liver weight, body mass index and abdominal fat thickness, were lower among SCD victims aged ≥ 80 years than among victims aged < 80 years. In those with IHD as etiology of SCD, at least 75% stenosis in one or more major coronary vessels was more common in SCD victims aged ≥ 80 years than among victims aged < 80 years (P=.001). Dying in sauna was more common among those ≥ 80 years than among those < 80 years (5.5% vs. 2.6%, P<.001). Conclusion In victims of unexpected SCD aged ≥ 80 years, the autopsy-based etiology of SCD was more commonly IHD than in those aged < 80 years. In SCD victims aged ≥ 80 years, severe fibrosis in myocardium, representing arrhythmic substrate, was more common than in the younger ones.